DABIGATRAN ETEXILATE FOR THE TREATMENT OF VENOUS THROMBOEMBOLIC COMPLICATIONS - N. M. Vorobieva; E. P. Panchenko («REMEDIUM GROUP» Ltd., 2015)
This article discusses the significant features and use of new oral anticoagulant dabigatran etexilate for the treatment of venous thromboembolic complications (VTC). The article presents the results of 4 randomized clinical studies: RE-COVER, RE-COVER II, RE-MEDY and RESONATE. The RE-COVER and RE-COVER (II) studies compared the effectiveness and safety of dabigatran and warfarin in patients with acute episode of VTC, and RE-MEDY and RESONATE studies assessed the prolongation of dabigatran therapy in patients with VTC, who completed the main 3-6-month course of anticoagulant therapy. In addition, REMEDY study estimated efficacy of dabigatran compared with warfarin, and RE-SONATE study estimated one compared with placebo. RE-COVER, RE-COVER II and RE-MEDY showed that the efficacy of dabigatran (150 mg 2 times a day) for the prevention of recurrent and fatal episodes of VTС was not less than that of warfarin; on top of that, dabigatran was more efficient in reducing the risk of hemorrhag-ic complications. In RE-SONATE study, dabigatran showed a 92% reduction in risk of the VTC relapse compared to placebo, but a 2.9-fold increase in risk of large or small clinically significant bleeding.